Sclerostin and Osteocalcin: Candidate Bone-Produced Hormones - Wang, Jialiang S.; Mazur, Courtney M.; Wein, Marc N. (Frontiers in Endocrinology, 2021)
Bone remodeling is balanced by two processes: bone formation and bone resorption. In addition to its structural role, the skeleton also serves as an endocrine organ that controls mineral metabolism and energy homeostasis. As a dynamic tissue, bone is formed and maintained by three major cell types: osteoblasts, osteoclasts, and osteocytes. Osteoblasts originate and differentiate from skeletal stem cells and are responsible for the synthesis of type I collagen and the deposition of mineralized matrix during bone formation. Osteocalcin has been identified as one of the osteoblast-derived endocrine hormones that regulates the biological processes of multiple target organs including pancreas, liver, muscle, adipose, testes, and the central and peripheral nervous system. In contrast, sclerostin is predominantly produced by osteocytes, terminally-differentiated osteoblasts embedded within mineralized bone matrix. A major role for sclerostin has been defined as a paracrine-acting regulator of WNT signaling and activity of osteoblasts and osteoclasts on bone surfaces. In addition to this important paracrine role for sclerostin within bone, sclerostin protein has been noted to act at a distance to regulate adipocytes, energy homeostasis, and mineral metabolism in the kidney. In this article, we aim to bring together the information relating to osteocalcin and sclerostin in systemic homeostasis. We summarize the current state of knowledge on animal models and human physiology related to these bone-derived factors. We will review multiple functions of osteocalcin and sclerostin in bone and other target organs. Finally, we highlight areas in which future research is expected to yield additional insights into the biology of osteocalcin and sclerostin.